PENERAPAN PENDEKATAN KONTEKSTUAL DALAM MATERI OPERASI BENTUK ALJABAR DI KELAS VII MTs NEGERI 2 PONTIANAK - Muhammad Ikhsan; Zubaidah Bistari; Bistari Bistari (Universitas Tanjungpura, 2019)
AbstractThis research was aimed to know and describe the effectiveness of contextual approach in the algebraic expression topic at Class VII MTs Negeri 2 Pontianak. The aspects that want to be know and describe are the implementation of the learning process, student’s learning activites, and student’s outcomes. The research method is descriptive method. The research subject is student in class VII E. Base on the data analysis from three aspects are: (1) the implementation of the learning process categorized good with average score 3,45; (2) student’s learning activities categorized active (69,21%); (3) students’s outcomes is not reached classical completeness with only 69,44% of student can achieve the minimum completeness criteria. Because only two out of three aspects that achieved, the coclusion of this research is the implementation of contextual approach less effective in the algebraic expression topic at class VII E MTs Negeri 2 Pontianak. Keywords: Contextual Approach, Implementation of Learning Process, Learning Activities, and learning outcome’s